Propuesta de un sistema de gestión por procesos en el área de poscosecha de la florícola Sanbelflowers CIa. Ltda. Ubicada en el sector Laigua de Maldonado, parroquia Alaquez, cantón Latacunga, provincia de Cotopaxi. - Sánchez Grandes, María del Carmen (2017)
The investigation of the project was carried out in the floriculture SANBELFLOWER CIA. LTDA. with the objective of developing a process management system for the post-harvest area in its facilities, carrying out the analysis and in turn complying with the technical-legal aspects that are applied in the company, taking into account the lack of procedures in their work. By work area, the respective analysis was carried out with several visual inspections, data gathering and weighting, which later allowed obtaining the real problem.